MENINGKATKAN HASIL BELAJAR MAHASISWA JURUSAN BAHASA INGGRIS PADA MATA KULIAH ENGLISH MORPHOLOGY DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF METODE JIGSAW - Rasuna Talib (Jurnal Inovasi, 2009)
The English Department Students of Faculty of Letters have low motivation in learning the subjects of linguistics, such as English Morphology. They felt bored and hard to follow this subject. This was probably because of the lowest creativity of the lecturers in creating the various model, methods or techniques in teaching linguitics subject. Consequently, most of students achievement are low. Thus, this makes me to conduct a reserarch by using the model of cooperative learning-jigsaw method. The objective of teaching is to increase students understanding toward the concepts in English morphology subject and to to increase the students learning achievement in English morphology subject. This research was conducted at the the English Department students of Faculty of Letters and Culture who programme the subject of English morphology in the academic 2006/2007 (39 students). The development method used in this teaching was the Classroom Action Research. It was conducted 3 cycles. about both teacher and students activites in the teaching and learning process, test and students feedback about the teaching and learning process The data are analyzed quatitatively and qualitatively. The result of research indicates that the jigsaw method can increase the achievement of English Department Students in learning English Morphology. This is proven by the result of students achievement in the cycle one 79% or the value 3 ( good category), in the cycle two 86% or the value 3,53 ( excellent category), and in the cycle three 90% or the value 3.71 ( excellent category). Besides, the impact of the applying of this method can make students active in the classroom. This is believed that the application of jigsaw method can give a valuable contribution for the increasing of teaching quality, both the students academic and social skills.